2020
DOI: 10.1111/all.14159
|View full text |Cite
|
Sign up to set email alerts
|

Deserters on the atopic march: Risk factors, immune profile and clinical outcomes of food sensitized–tolerant infants

Abstract: Background: A few studies have investigated the antecedents and outcomes of infants who demonstrate IgE sensitization to foods that they clinically tolerate. Improved understanding of this sensitized-tolerant phenotype may inform strategies for the prevention of food allergy. Methods:In an Australian birth cohort (n = 1074), assembled using an unselected antenatal sampling frame, participants were categorized as nonsensitized (NS), sensitizedtolerant (ST), or food allergic (FA) based on skin prick testing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
3
8
0
Order By: Relevance
“…Similar to previous studies [2,17,19,[27][28][29], we found that family history of allergy was strongly associated with increased OR of childhood asthma and allergic diseases. Longer breastfeeding duration could reduce these ORs.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to previous studies [2,17,19,[27][28][29], we found that family history of allergy was strongly associated with increased OR of childhood asthma and allergic diseases. Longer breastfeeding duration could reduce these ORs.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to previous studies [2,17,19,[27][28][29], we found that family history of allergy was strongly associated with increased OR of childhood asthma and allergic diseases. Longer breastfeeding duration could reduce these ORs.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to previous studies [2,17,19,[27][28][29], we found that family history of allergy was strongly associated with the risk of childhood asthma and allergic diseases. Longer breastfeeding duration could reduce these risks.…”
Section: Discussionsupporting
confidence: 91%